P239 TOLERABILITY OF SACUBITRIL/VALSARTAN TREATMENT IN OLDER PATIENTS WITH HEART FAILURE WITH REDUCED EJECTION FRACTION: PRELIMINARY DATA FROM THE REAL–WORLD AGING–HF REGISTRY. (18th May 2022) - Herbst, A; Orso, F; Camartini, V; Virciglio, S; D'Errico, G; Salucci, C; Verga, F; Fattirolli, F; Marchionni, N; Di Bari, M; Ungar, A; Baldasseroni, S
Abstract: Background: Although older patients with heart failure (HF) with reduced ejection fraction enrolled in PARADIGM–HF showed a good tolerance to sacubitril/valsartan (Sa/Va), more real–word data are needed to define their tolerability in this population. Aim: To describe the Sa/Va tolerability and titration in older HFrEF patients followed by our HF outpatient. Methods: HFrEF patients aged ≥65 years and treated with Sa/Va from November 2016 to June 2021 were enrolled, assessing Sa/Va tolerability at six months and its clinical and hemodynamic effects. Results: We enrolled 101 patients with a mean age of 78 years (⁓20% female). The aetiology was ischemic in 59% of cases while the mean ejection fraction was 31%. Sa/Va was prescribed at the starting dose (24/26mg) and intermediate dose (49/51mg) in 91% and 9% of cases, respectively. After six months, 9 of the 100 patients still alive had discontinued treatment with Sa/Va (4 for symptomatic hypotension, 3 for suspected allergic reaction and 2 for worsening renal function). Of the 91 patients still on therapy, only 17 had reached the target dose (97/103mg) while 28 were at the intermediate dose (Figure 1 ). Symptomatic hypotension (62%), hyperkalaemia (15%) and worsening of renal function (4%) were the main causes of maintaining Sa/Va therapy at the starting dose; note, in 15% of cases a specific cause of non–titration was not identified. Comparing HF treatment between starting dose vs higher–dose patients, after six months in low–dose patients there was a slight improvement in mineralcorticosteroid receptor antagonist (MRA) prescription and in combination therapy (Sa/Va, beta–blocker and MRA) while in patients at higher–doses there was a significant decrease (Figure 2 ). In patients still receiving Sa/Va, significant clinical improvement was observed while renal function, K+ levels and systolic blood pressure remained stable (Figure 3 ). Conclusions: After six months of treatment, Sa/Va was well tolerated in most of our older patients and used in combination with a beta–blocker and an MRA in a high percentage of cases, although a reduction in MRA prescription is observed in patients taking higher dosages of Sa/Va. In addition, there was a marked improvement in the clinical variables.